TBK1 phosphorylates mutant Huntingtin and suppresses its aggregation and toxicity in Huntington's disease models. (5th August 2020) - Hegde, Ramanath Narayana; Chiki, Anass; Petricca, Lara; Martufi, Paola; Arbez, Nicolas; Mouchiroud, Laurent; Auwerx, Johan; Landles, Christian; Bates, Gillian P; Singh‐Bains, Malvindar K; Dragunow, Mike; Curtis, Maurice A; et al.
Abstract: Phosphorylation of the N‐terminal domain of the huntingtin (HTT) protein has emerged as an important regulator of its localization, structure, aggregation, clearance and toxicity. However, validation of the effect of bona fide phosphorylation in vivo and assessing the therapeutic potential of targeting phosphorylation for the treatment of Huntington's disease (HD) require the identification of the enzymes that regulate HTT phosphorylation. Herein, we report the discovery and validation of a kinase, TANK‐binding kinase 1 (TBK1), that efficiently phosphorylates full‐length and N‐terminal HTT fragments in vitro (at S13/S16), in cells (at S13) and in vivo . TBK1 expression in HD models (cells, primary neurons, and Caenorhabditis elegans ) increases mutant HTT exon 1 phosphorylation and reduces its aggregation and cytotoxicity. We demonstrate that the TBK1‐mediated neuroprotective effects are due to phosphorylation‐dependent inhibition of mutant HTT exon 1 aggregation and an increase in autophagic clearance of mutant HTT. These findings suggest that upregulation and/or activation of TBK1 represents a viable strategy for the treatment of HD by simultaneously lowering mutant HTT levels and blocking its aggregation. Synopsis: Phosphorylation of Huntingtin protein at S13 and S16 plays a vital role in regulating its aggregation, clearance, and toxicity. TBK1, a natural kinase that phosphorylates HTT at S13, leads to the reduction of mutant HTT aggregates in cells and C. elegans via a mechanism that requires both HTT S13 phosphorylation and autophagy. Identification of a novel kinase, TBK1, that efficiently phosphorylates both wildtype and mutant HTT at residue serine 13. TBK1 overexpression increase S13 phosphorylation on mutant HTT, inhibits its aggregation and promotes autophagic degradation of soluble, but not preformed aggregates of HTT. TBK1 overexpression protects against mutant HTT cytotoxicity in neuronal and C. elegans models of HD. Increased phosphorylation at serine 13 or promoting mutant HTT autophagic clearance represent viable therapeutic strategies for the treatment of HD. Abstract : Phosphorylation of the N‐terminal domain of Huntingtin (HTT) by TANK‐binding kinase 1 (TBK1) promotes its autophagic clearance and reduce its aggregation and cytotoxicity, suggesting new strategies for neuroprotective therapies.